The Early Permian active continental margin and crustal growth of the Cathaysia Block: In situ U–Pb, Lu–Hf and O isotope analyses of detrital zircons - Li, X.; Li, Zheng-Xiang; He, B.; Li, W.; Li, Q.; Gao, Y.; Wang, Xuan-Ce (Elsevier Science BV, 2012)
Late Permian to Triassic (“Indosinian-aged”) orogenesis and associated magmatism are widespread in southeastern China, but their causes and significance to the regional geodynamic evolution are highly controversial. We report in this study integrated in situ U–Pb, Hf and O isotope analyses of detrital zircons from the Middle to Late Permian sediments in southeastern China, and use these data to decipher the sedimentary provenances, regional magmatic barcode and crustal evolution processes. A total of 409 concordant U–Pb zircon analyses on five sedimentary samples exhibits four major age peaks at ca 1870 Ma, ca 445 Ma, ca 370 Ma and ca 280 Ma, one “broad” age group of ca 1180–960 Ma, and two subordinate peaks at ca 2530 Ma and ca 800 Ma. All the Archean-aged detrital zircons are oval in shape with clear abrasive imprints, indicating long-distance transport and/or multi-cycled sedimentary processing from unknown Archean sources. In contrast, detrital zircons of the remaining age groups are mostly euhedral to subhedral crystals, suggesting short-distance transport. Zircon ages of ca 1870 Ma, ca 1180–960 Ma, ca 800 Ma, ca 445 Ma and ca 280 Ma are coeval with exposed magmatic rocks in the Cathaysia Block of southeastern China. The ubiquitous existence of ca 280 Ma detrital zircons in the studied sediments implies a widespread occurrence of Early Permian magmatic rocks in southeastern China coastal region.In situ Hf and O isotope analyses of detrital zircons reveal periods with growth of juvenile continental crust at ca 1870 Ma, ca 1400 Ma, ca 1140–940 Ma, ca 445 Ma and c. 280 Ma, alternating with reworking and recycling of continental crust at ca 1200 Ma, ca 830 Ma and ca 370 Ma. The ca 280 Ma detrital zircons display coherent, negative correlations between εHf(T) and δ18O values, indicating that their igneous source rocks probably formed with reworking of ancient supracrustal materials by mantle-derived magmas in an active continental margin. This interpreted ca 280 Ma magmatic event in an active continental margin is coincident with the remarkable change in regional palaeogeography from a carbonate platform in Carboniferous-earliest Permian time to an elongated uplift along the southeastern coastal regions in mid-Early Permian. Therefore, the early Indosinian tectonism and magmatism in southeastern South China most likely reflect the formation of a continental arc by the subduction of the Paleo-Pacific plate in the Early Permian.